The Cultural Communication Based on the Philosophy Of Lampung, Indonesian Society in Traditional Wedding - Kartika, Tina; Meutia, Intan Fitri (Journal of Ecohumanism, 2025)
Indonesia with its diverse tribes, cultures, religions is a society that must be able to appreciate the differences. The custom of marriage is one of the relationships with significant cultural communication. This research was conducted in the Lampung Province, one of Indonesia’s provinces. The province of Lampung has two distinct traditions: pepadun and saibatin. The topic of this study is traditional Saibatin marriage. The aim of this study is to describe cultural communication based on Lampung philosophy in wedding traditions. The approach is based on the qualitative concept and involves focus group discusses and informant interviews. More sources are found in different media journals. The finding of cultural communication based on Lampung ethnic philosophy is seen from wedding rituals. Both verbal and nonverbal communication is present in wedding customs. Verbal communication uses Lampung language with Nyo and Api dialect. Symbols as nonverbal communication are : cakes, dodol (a typical food made from flour, brown sugar and coconut milk), nireh ugay tools or sirih pinang (set of tools for chewing betel), gold, jewelry, diamonds, jung syarat cloth. After the wedding, the bride is invited to the groom’s house by riding a rato/palanquin and accompanied by balak percussion (a typical Lampung musical instrument).